Virtual Music Concert as a Transformation of Autistic Individual Art Performance during the Covid-19 - Chrisdina Chrisdina; Yolanda Stellarosa; Greta Ariati Mulyosantoso; Nurul Hidayah; Kimberly Gavrila Haranata (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
During the Covid-19 pandemic, changes in the platform for expressing themselves through art performance are also faced by autistic individuals. This is certainly a challenge because music is a way that is used by autistic individuals to express themselves. Supporting by social media like YouTube; platform transformation brings ideas for art performance organizers so that autistic individuals can continue to perform, one of which is through the Autism Awareness Festival. Through computer-mediated communication models and diffusion of innovation theory, this study aims to dissect how the adaptation process that occurs in autistic individuals conveys self-expression through performance and digital art performance models in the form of virtual concerts, and how the concept of virtual art performance communicates the big message from the AAF. This study uses a qualitative method. Data collection techniques through FGDs were divided into two groups of AAF participants; and one group of participating parents. In-depth interviews were conducted with the organizers and accompanying teachers. The result shows that the concept of virtual concert can be applied to autistic individuals. The process that occurs in these conditions looks unique at the stages of the period in which there are adaptations and rejections. At the stage of the social system that must be targeted first are parents and aides; as a support system that becomes a bridge to explain a new concept. Autistic individuals have a very small and close environment, so input from parents and guardians is the most trusted source of information for them.